THE EFFECT OF BREAST CARE AND GYMNASTICS ON MOTHERS WITH LESS BREAST MILK PRODUCTION: A LITERATURE REVIEW - Rasulina Br Peranginangin; Mardiana Ahmad; Andi Nilawati Usman; Nur Aliya Arsyad (Nurse and Health: Jurnal Keperawatan, 2022)
Background: The low coverage of exclusive breastfeeding shows that not many mothers succeed in exclusive breastfeeding. In post-partum mothers often because the pain experienced after childbirth makes the mother lazy to breastfeed the baby; this can cause the production of breast milk to be uneventful due to lack of stimulation in the breast so that the oxytocin cycle is not smooth and causes breast milk not to come out. Objectives: This study aimed to find out the Effect of Breast Care and Gymnastics on Mothers with Less Breast Milk Production. Design: This research design is the study of literature by descriptive methods. Data Sources: Search articles using the Mendeley app with a period of 2017 to 2021 by entering the keyword" "breast care, breastfeeding mothers, less milk production. Articles selected based on: Inclusion Criteria that articles related to breast care in nursing mothers, year of publication 2017-2021, international Publications, articles using English, original articles, abstracts, full text, and open access. Exclusion Criteria that articles other than English and It doesn't have DOI. There were 13 articles based on inclusion criteria. Review Methods: A systematic review method based on established criteria, then collected and made a journal summary including the researcher's name, the year of publication of the journal, the title of the study, the method, and an overview of the results or finding. Results: The 13 articles that reviewed and met the inclusion criteria, it was concluded that breast care and gymnastics in breastfeeding mothers significantly influenced breast milk production. This is due to the presence of touch in the breast that stimulates the mammary glands. Conclusion: Breast care and gymnastics have a significant effect on increasing milk production in breastfeeding mothers.